An Energy Efficient Secure routing Scheme using LEACH protocol in WSN for IoT networks - Suresh, Bhukya; Shyama Chandra Prasad, G. (Measurement. Sensors, 2023)
One of the most recent and exciting new applications can be found in the realm of the IoT, which makes it possible to connect various objects or devices over the internet. Many options exist to mitigate the negative effects of communication protocols on WSNs' power consumption. LEACH protocol is a cluster-based one, that uses clusters to divide the network. LEACH uses the random numbers produced by each sensor node to choose a group of nodes to serve as cluster heads (CHs). An enhanced version of the LEACH procedure for stable & energy-efficient CH selection is the subject of the proposed work. The proposed work stabilizes the random number generation by including Rank-based CH selection using Node coverage, Energy consumption rate, and the characteristics of the base station's distance. The node coverage parameter guarantees that the chosen CHs have more neighbors in their coverage circle, it, in turn, lowers the energy required for member nodes to go to the CH. The quantity of energy used rate ensures that the selected CHs have higher energy. According to the findings of the simulations, it is clear that the suggested strategy significantly improves the Energy efficiency performance of WSNs, network longevity, and communication quality.